The impact of self-compassionate mindfulness on online learning behavioral engagement of international students during COVID-19: Positive emotion and self-improvement motivation as mediators - Chen, Junmei; Lin, Guoyao; Lyu, Yong (Frontiers in Psychology, 2022)
Focusing on the domain of self-compassion, this study explored the promotion mechanism of online learning behavioral engagement of international students in China under COVID-19. Positive emotion and self-improvement motivation were selected as mediators. Participants were 606 international students from 8 countries who were studying online in their own countries due to the international travel restriction of COVID-19. Results showed positive emotion and self-improvement motivation completely mediated self-compassionate mindfulness and online learning behavioral engagement of international students. Positive emotion and self-improvement partially mediated self-compassionate mindfulness and online learning behavioral engagement of international students respectively. Students with higher self-compassionate mindfulness engage with online learning more in that they possess more positive emotion and self-improvement motivation. This study suggested that self-compassionate mindfulness may facilitate online learning behavioral engagement via positive emotion and effective self-improvement motivation.